(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In the past, the land that is currently part of Jaipur City was referred to as ’Matsya Desh.’ In theMahabharata, it was the realm of King Virat. Rajasthan’s lovely Pink City Jaipur, was the stronghold of aclan of monarchs whose three hill forts and series of palaces in the city are important attractions. Knownas the Pink City because of the hue of the stone used solely in the walled city, Jaipur’s bazaars offerembroidered leather shoes, blue ceramics, tie and dye shawls and other unusual products. WesternRajasthan itself forms a handy circuit, in the center of the Thar desert which has affected its history,lifestyles and architecture. The contemporary industrial economy and the creation of additional jobshave both benefited from the increased focus on industrialization as the world’s population has grown.The official system has also been put into place. Jaipur’s efforts to become an industrial hub are beingsupported by the Rajasthan Industrial and Investment development Policy 2010.